2011
DOI: 10.1111/j.1574-6968.2011.02325.x
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal third of the BinB subunit from the Bacillus sphaericus binary toxin is sufficient for its interaction with midgut receptors in Culex quinquefasciatus

Abstract: Heterodimeric binary (Bin) toxin, the major insecticidal protein from Bacillus sphaericus, acts on Culex quinquefasciatus larvae through specific binding to the midgut receptor Cqm1, a role mediated by its 448-amino-acid-long BinB subunit. The molecular basis for receptor recognition is not well understood and this study attempted to identify protein segments and amino acid motifs within BinB that are required for this event. First, N- and C-terminally truncated constructs were evaluated for their capacity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…Furthermore, direct‐binding and homologous‐competition assays showed that Cry49Aa toxin surprisingly had a slightly lower binding capacity than Cry48Aa to BBMFs from C. quinquefasciatus . Therefore, we considered that Cry49Aa also carried the receptor binding site, responsible for the binding to the apical membrane of midgut epithelium cells in C. quinquefasciatus , which was consistent with previous results for the related proteins of the toxin_10 family, such as BinB and Cry35Ab1 (Schnepf et al ., ; Romao et al ., ). In addition, the results of competition binding assays between biotin‐labelled Cry49Aa and unlabelled truncated Cry49Aa proteins showed that the C‐terminus of the Cry49Aa subunit was the region involved in BBMF binding, and only a limited C‐terminal fragment located between S349 and N464 is essential and sufficient for receptor binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, direct‐binding and homologous‐competition assays showed that Cry49Aa toxin surprisingly had a slightly lower binding capacity than Cry48Aa to BBMFs from C. quinquefasciatus . Therefore, we considered that Cry49Aa also carried the receptor binding site, responsible for the binding to the apical membrane of midgut epithelium cells in C. quinquefasciatus , which was consistent with previous results for the related proteins of the toxin_10 family, such as BinB and Cry35Ab1 (Schnepf et al ., ; Romao et al ., ). In addition, the results of competition binding assays between biotin‐labelled Cry49Aa and unlabelled truncated Cry49Aa proteins showed that the C‐terminus of the Cry49Aa subunit was the region involved in BBMF binding, and only a limited C‐terminal fragment located between S349 and N464 is essential and sufficient for receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…As the strongest interaction with Cry48Aa was observed with the smallest N‐terminal fragment of Cry49Aa, it is most probable that the Cry48Aa ‐binding site is localized between residues N49 and S149. These results are similar to previous work that showed that the receptor binding site of the BinB subunit is located in its N‐terminal region (Romao et al ., ; Tangsongcharoen et al ., ), whereas the C‐terminal region was able to interact with BinA (Limpanawat et al ., ). Thus, we inferred that Cry49Aa plays an important role in the mechanism of action of these two‐component toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Residue 150 was suggested to be important in receptor binding by BinB (Singkhamanan et al, 2010) and further, recent work has identified the region from residues 33-158 to be important for receptor binding, with residues 147-149 being critical to binding (Romao et al, 2011). In another study, mutants in the N-and C-termini of each protein that alone were found to eliminate toxicity were found to complement each other to restore toxicity when mixed (Shanmugavelu et al, 1998).…”
Section: Bin Structurementioning
confidence: 93%
“…Binding of BinB to target membranes appears to be mediated by residues at its N-terminal end (Oei et al, 1992;Romao et al, 2011;Singkhamanan et al, 2010), consistent with receptor recognition via the head domain (Srisucharitpanit et al, 2014). The BinA/BinB toxin appears to bind to a single toxin receptor, a GPI anchored -glycosidase (Silva-Filha et al, 1999), which may simplify the investigation of binding interactions (particularly when compared to the complex receptor binding of 3-domain toxins).…”
Section: Sphaericus B Thuringiensis Bacillus Cereus and Paenibamentioning
confidence: 99%